ANALISIS PUTUSAN MAHKAMAH AGUNG NOMOR 738 K/PDT/2023 TENTANG WANPRESTASI DALAM PERJANJIAN JUAL BELI TANAH ANTARA PT BUKIT KAMSIRI INDAH DAN PT TANJUNG BUTON INTERNASIONAL - Aura Prameswari Wirasmara; Elisabeth Hana Gracesoldy Sihombing; Kayla Mahiya Putri Wibowo; Nindia Rifdah Fakhirah (Jurnal Riset Multidisiplin Edukasi, 2025)
The case between PT Bukit Kamsiri Indah and PT Tanjung Buton Internasional originated from a land sale and purchase agreement documented in several notarial deeds. However, the Defendant did not perform the agreement properly. As a result, this dispute reached the cassation level. For this reason, the normative legal method was used in this study to examine how the courts, particularly the Supreme Court, assessed the breach of contract and determined the responsible party. The results of the discussion show that third parties are irrelevant to the Supreme Court because this case is merely a matter of contract enforcement. In addition, the panel of judges reaffirmed the principle of pacta sunt servanda, which means that the parties remain bound by the terms of a validly made agreement.